1996
DOI: 10.2351/1.4745413
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies of thick-section cutting with a chemical oxygen–iodine laser (COIL)

Abstract: A simple mathematical model of thick-section stainless steel cutting with a high power chemical oxygen–iodine laser (COIL) is presented and compared with experimental results obtained with a 10-kilowatt COIL at the U.S. Air Force's Phillips Laboratory. This model uses a lumped-parameter technique to relate the cutting kerf depth with various process parameters and can be used to predict scaled laser materials processing performance to very thick sections. The model is similar to an empirical model developed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The kerf width Wk was measured after the tests using a caliper. As observed by Kar [5] and Carroll [61, for a given cut, the kerf width generally increased with increasing cut depth. In these cases, an averagekerf width was obtained by summing the width at several locations along the edge of the target and dividing this result by the number of measurements.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…The kerf width Wk was measured after the tests using a caliper. As observed by Kar [5] and Carroll [61, for a given cut, the kerf width generally increased with increasing cut depth. In these cases, an averagekerf width was obtained by summing the width at several locations along the edge of the target and dividing this result by the number of measurements.…”
Section: Methodssupporting
confidence: 66%
“…Using Equations and fromSiegman [16] an estimate of the maximum number of modes which could be lasing is calculated to be 34; this issignficantly fewer than the estimated 200 modes with the rectangular beam used by Kar eta!. [5] and Carroll and Rothenflue [6]. The advantage of using the apertured Z-pass resonator configuration is that it permits a much better optical quality beam while maintaining typical RADICL power levels by increasing the total gain length via the three passes through the COIL gain medium, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that Nd:YAG laser resulted in improved cut quality as compared to CO 2 laser cutting. Thick section cutting of stainless steel was examined by Kar et al (1996). They modeled the cutting process and compared the predictions of the kerf size with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…They also presented a simple two-parameter model and empirically determined these two parameters by fitting the model to their experimental data in order to predict the scaled cutting capability of COIL. Kar et al 5 produced a more complete data base for stainless steel cutting with an inert gas assist. Kar et al also demonstrated the thick-section cutting capability of COIL and development a simple theoretical cutting model.…”
Section: Introductionmentioning
confidence: 99%